الرھن الحیازي بین قواعد التكوین وقواعد التضمین للمرتھن: دراسة قانونیة مقارنة بالفقه الإسلامي - المعموري، معتز محمود (جامعة بابل - كلية القانون, 2015)
لما كان مقصود الرهن , الاستيثاق باليدن للتوصل لاستيفاءه من ثمن المرهون , إذا عجز الراهن عن الوفاء به في الأجل المحدد للوفاء , فلا يتحقق هذا المقصود إلى اذا قام اطراف العقد بتنفيذ ما عليهم من التزامات مصدرها الاتفاق الذي المبرم بينهما , والذي يعد أي إخلال ببنوده من قبل المرتهن موجباً لضمانه , لذا فإن لقواعد الرهن الحيازي صلة وثيقة بضمان المرتهن للمال المرهون , تلك الصلة التي عالجها الفقهاء المسلمون في كتاباتهم ونصوص القوانين المدنية المقارنة , ولأهمية هذا الموضوع والإشكاليات التي يثيرها كونه لم يتم بحثه سابقاً سنبحثه في ثلاث مباحث , نخصص المبحث الأول منها للتعريف بالرهن الحيازي , ونقسمه على مطلبين , ونعقد المبحث الثاني لتكوين الرهن الحيازي ونقسمه على مطلبين , ثم نفرد المبحث الثالث لعلاقة الرهن الحيازي بقواعد ضمان المرتهن ونقسمه على مطلبين. ونتبعها بخاتمة نضمنها أبرز النتائج والمقترحات التي توصلنا اليها من خلاله.
What was intended foreclosure, ascertained Balidn to reach Kims of the price of the mortgaged , if the inability of the current meet him at the deadline to meet , then this is achieved is intended to if the parties to the contract to implement what they have obligations originating from the agreement concluded between them , which is any breach of its terms of pre-bonded positive for guaranteed , so the rules of the foreclosure possessory closely related to ensuring the mortgagee for money mortgaged , those relating addressed by Muslim jurists in their writings and texts of the laws of the comparator , and the importance of this topic and the dilemmas posed by being not been discussed previously Senbgesh in three sections , we devote section of which the first the definition of mortgage- possessory , and divide it by two demands , and we hold the second section of the formation possessory lien and divide it by two demands , then single out the third section of the relationship of possessory mortgage rules to ensure the mortgagee and divide it by two demands . And we follow the most prominent conclusion Ndmnha results and proposals that we reached through.
Keywords: القوانين والتشريعات -- قانون الرهن -- النصوص الشرعية -- الفقه الإسلامي -- المقدرة المالية -- نظام الرهن -- مستخلصات الأبحاث